Тренди UI дизайну у 2021 році - Боровинська, Ю. Д. (ХНУРЕ, 2021)
User interface (UI) design is the process designers used to build interfaces in software or computerized devices, focusing on looks or style. Designers aim is created interfaces which users find easy to use and pleasurable. Design should be “invisible”: users shouldn’t focus on it but on completing tasks. UI should be enjoyable (or at least satisfying and frustration-free). UI also should be in trend. Design innovations attract user’s attention, so they will keep returning.
Keywords: UI дизайн; шрифт